Widespread transmission of distinct genetic lineages of Murray Valley encephalitis virus in Australia, 2008-2009 - Williams, David; Diviney, Sinead; Niazi, A.; Herring, B.; Johansen, C.; MacKenzie, John (International Union of Microbiological Societies, 2011)
Murray valley encephalitis virus (MVEV) is the most important cause of arboviral neurological disease in humans in Australia. Increased activity of MVEV was observed in Australia in 2008 and 2009, leading to fatal human and equine cases, and renewed concerns regarding its potential to spread and cause disease. Four genotypes (G1-G4) of MVEV are recognised: G1 and G2 contain strains from the Australian mainland (and recent strains from Papua New Guinea), while single PNG isolates comprise G3 and G4. Complete prM-Env genes were sequenced from over 50 MVEV strains from different regions of Australia and PNG, and from different times, in order to establish genetic relationships between recent circulating strains with earlier isolates. Phylogenetic analyses showed that G1 was the dominant circulating genotype sampled over a 60 year period. Two distinct sub-lineages of G1 were observed: G1A comprised the prototype strain, recent PNG isolates as well as 2008 and 2009 Western Australian strains; G1B included early Western Australian viruses (isolated from 1972) and including 2009 (but not 2008) strains and all 2008 isolates from eastern Australia.The finding that 2008 strains from eastern Australia and Western Australia belonged to different sub-lineages suggests these originated from distinct foci of activity in this year, and raises questions regarding the transmission and spread of MVEV within Australia. An additional finding of importance was the identification of G2 strains for the first time since 1995. Unlike earlier G2 strains, isolated in the northeast Kimberley region, recent G2 viruses were found in the western and southern parts of Kimberley, indicating this genotype has a broader geographic distribution than first thought. The demonstration of co-circulation of three distinct genetic lineages (G1A, G1B and G2) of MVEV in northwestern Australia provides further evidence that it has an enzootic focus there.